The Students' Ability in Writing English Exposition Texts: Descriptive Study at the Second Grade of Senior High School of Hangtuah 3 Mataram in Academic Year 2016-2017 - Muslimin Muslimin (Muhammadiyah University of Mataram, 2017)
The population of this research was the second-grade students of SMA 3 Hangtuah Mataram in academic year 2015/2016 which consist of 2 classes. It means that all of the population was 30 students and this population makes sample 30 students’. The thesis aimed to find out the student’s ability in writing English exposition text: descriptive study at the second grade of senior high school of Hangtuah 3 Mataram in academic year 2015/2016. The researcher took 30 students of the second years' students of Hangtuah 3 Mataram to be respondents/sample, the population only two classes consists of 30 students. In collecting data, the researcher used a writing test. The students were asked to make a paragraph in exposition text. The data analysis, the students score was found that student’s ability in writing English exposition text as good in 2 class (30 students), in this case, in class 2 there are no students got excellent , 20 students got good level (67%), 8 students got very good criteria (26%), and 2 students got fairly good criteria (7%). Based on the result above it can be concluded that the students' ability in writing English exposition text 20 students “good” criteria or 67%.